A new test setup for simulation of the combined effect of bending and axial restraint in slab-like specimens. (15th December 2020) - Gomes, J.G.; Granja, J.; Sousa, C.; Zahabizadeh, B.; Faria, R.; Schlicke, D.; Azenha, M.
Highlights: Development of restraint device to control the axial load in slab-like specimens. Experimental study on the combined effect of restrained deformation and bending. Monitorization of the higro-mechanical behaviour in controlled environment. Detailed presentation of experimental conditions and results. Applied force to restrain deformations is coherent with the state-of-the-art. Abstract: This paper presents a long-term experimental campaign for simulation of the combined effects of restrained shrinkage and vertical loads on reinforced concrete (RC) slabs, performed in the scope of the research project "IntegraCrete: a multi-physics and multi-scale approach to the combined effects of applied loads and thermal/shrinkage deformations in reinforced concrete structures". A new experimental method is applied, in which a restraining device is used to constrain the axial deformation of a slab-like specimen, while allowing it to simultaneously endure bending and shear stresses. The deformation is restrained by two hydraulic actuators connected to one of the slab extremities, allowing a progressive adjustment of the axial force installed whilst controlling the deformation on a pre-defined region (active restraint). The experimental program comprehends the long-term testing of slabs, in a controlled environment room, under four distinct situations by combining the two following conditions: (i) with or without restraint to axial deformations and (ii) with or without application of vertical loads. The structural behaviour of the slabs is continuously monitored over a period of 15 months, while several mechanical properties, as well as the internal relative humidity (RH) of concrete, are assessed in complementary specimens from the same batch. The present work intends to contribute to a deeper understanding of the complex interactions that occur between self-imposed deformations (particularly due to drying shrinkage), concrete viscoelasticity and external loads in the process of crack development. It provides an important and unprecedented database for validation of numerical or analytical approaches for prediction of the structural behaviour of slabs subjected to the abovementioned effects.